Research on Resource Integration and Enterprise Performance of China Construction Environmental Energy’s Reverse Mixed Ownership Reform - Yan, Ziyang; Zhao, Binhan (Journal of Global Economy, Business and Finance, 2025)
This article explores the resource integration and corporate performance issues of China Construction Environmental Energy through the introduction of China Construction Qiming for reverse mixed ownership reform. As a private enterprise in the environmental protection industry, China Construction Environmental Energy faces challenges such as difficult financing and intensified market competition. By introducing strategic investors with state-owned background through reverse mixed ownership reform, it effectively expands financing channels, enhances financial strength, and improves market competitiveness and brand influence. The article provides a detailed analysis of China Construction Environmental Energy’s resource identification, acquisition, and integration strategies in the mixed ownership process, as well as the positive impact of these strategies on the company’s financial performance, market performance, innovation performance, and governance performance. The research results indicate that reverse mixed ownership significantly enhances the comprehensive strength and market value of China Construction Environmental Energy.